Development of a dispersive liquid–liquid microextraction (DLLME) method coupled with GC/MS as a simple and valid method for simultaneous determination of phthalate metabolites in plasma. Issue 14 (8th December 2017) - Amin, Mohammad Mehdi; Ebrahim, Karim; Poursafa, Parinaz
ABSTRACT: Phthalates are ubiquitous environmental contaminants, and frequent biological monitoring of their metabolites (as toxic species of phthalates in human body) is highly recommended. A novel dispersive liquid–liquid microextraction (DLLME) coupled with Gas Chromatography–Mass Spectrometry (GC-MS) has been developed for the determination of seven phthalate metabolites in human plasma for the first time. Plasma proteins were efficiently precipitated by adding of 0.2mg dry trichloroacetic acid to 10 mL plasma samples, incubation and centrifuging. For DLLME, a mixture of extraction solvent (chlorobenzene, 10 µL) and dispersive solvent (acetonitrile, 750 µL) were rapidly injected into 5.0 mL aqueous sample for the formation of cloudy solution, the analytes in the sample were extracted into the fine droplets of chlorobenzene. After extraction, phase separation was performed by centrifugation and the enriched analytes in the sedimented phase were subjected to GC-MS analysis. All important parameters affecting DLLME performance were investigated and optimised. Under the optimum extraction condition, the method yields a linear calibration curve for all target analytes in the concentration range from 5 to 5000 ng mL −1 . The limits of detection and relative standard deviations for all phthalate metabolites were between 1.21–2.09 ng mL −1 and 4.8–6.8%, respectively. This is a very simple, rapid and reproducible method, which requires low volume of sample and toxic solvents.